Upaya Penegakan Hukum Balai POM Di Kupang Terhadap Produksi Dan Penjualan Kerupuk Yang Mengandung Boraks - Kadja, Gracia Frederika; Dima, Adrianus Djara; Fanggi, Rosalind Angel (Artemis Law Journal, 2025)
Law enforcement efforts by the BPOM in Kupang were carried out by the BPOM Civil Servant Investigator (PPNS) by conducting an investigation based on sample results. During the 2021-2023 period, there was a surge in the discovery of foods containing borax with crackers being the most products. The formulation of the problem in this study is: (1) How are the law enforcement efforts by the BPOM in Kupang against the case of the discovery of crackers containing borax. (2) What is the inhibiting factor for the BPOM in Kupang in carrying out law enforcement efforts against the case of the discovery of crackers containing borax. The type of research used in this study is empirical juridical, namely in analyzing problems carried out by combining legal materials with data in the field. The results of the research obtained: (1) Law enforcement efforts by the BPOM were carried out by BPOM investigators based on the results of sample tests and investigations were carried out by investigators with the provision of administrative sanctions. (2) The factors that hinder law enforcement by the BPOM are due to; lack of investigators, lack of ability, understanding and awareness of actors, actors who sell from place to place, lack of optimal implementation of regulations, lack of awareness of parties collaborating with the BPOM, geographical conditions in the form of islands, and lack of community participation. Suggestions need to increase law enforcement in the food sector, especially in the production and sale of crackers with borax, increase in cooperation with parties who collaborate with the BPOM in socializing food security and the dangers of chemical additives, strict supervision of the distribution and sale of cracker products containing borax, and followed by increasing awareness of each sector in collaboration with BPOM.